Strategi Pengembangan Desa Petang Sebagai Desa Wisata Berbasis Masyarakat di Kabupaten Badung: Strategi Pengembangan Desa Petang Sebagai Desa Wisata Berbasis Masyarakat di Kabupaten Badung - Pranatajaya, I Gusti Ngurah Krisna; Tirtawati, Ni Made; Mertha, I Wayan (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2024)
This study aims to analyze internal and external existing conditions and formulate strategic factors in the development of Petang Village as a community-based tourism village in Badung Regency. This study adopts a qualitative approach by using interview guidance as the primary data collection instrument. The research sample consisted of 6 informants/resource persons where the Chairman of the Petang Village Porkdarwis was the key speaker, the Head of Petang Village was the main resource person and the supporting resources person representing various stakeholders, including the local community, the media, the government, and the tourism industry. Data analysis was carried out using the META SWOT with VRIO to identify internal factors and PESTEL to identify external factors faced in the development of Petang Tourism Village. The results of the analysis show that the Strength-Opportunity (SO) strategy is the most appropriate approach to optimize the potential of Petang Village. This strategy focuses on utilizing the internal strength of the village to capitalize on the external opportunities available. The results of this study indicate that the implementation of the SO strategy can effectively encourage the transformation of Petang Village into a more advanced and sustainable tourist destination.